2016
DOI: 10.1051/epjconf/201611908002
|View full text |Cite
|
Sign up to set email alerts
|

Saharan and Arabian Dust Aerosols: A Comparative Case Study of Lidar Ratio

Abstract: This work presents a first comparative study of the Lidar Ratio (LR) values obtained for dust particles in two singular dust-influenced regions: the Canary Islands (Spain, close to the African coast in the North Atlantic Ocean), frequently affected by Saharan dust intrusions, and the Kuwait area (Arabian Peninsula) as usually influenced by Arabian dust storms. Synergetic lidar and sun-photometry measurements are carried out in two stations located in these particular regions for that purpose. Several dusty cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Kuwait is a Middle Eastern developed country located at the northeast corner of the Arabian Peninsula and surrounded by the Persian Gulf. Because of its geographical location and climate change, it has been affected by droughts and frequent dust storms [10][11][12]. In recent years, regional military conflicts have contributed to more desertification in the area [13].…”
Section: Introductionmentioning
confidence: 99%
“…Kuwait is a Middle Eastern developed country located at the northeast corner of the Arabian Peninsula and surrounded by the Persian Gulf. Because of its geographical location and climate change, it has been affected by droughts and frequent dust storms [10][11][12]. In recent years, regional military conflicts have contributed to more desertification in the area [13].…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [37] reported similar results showing the lidar ratio is larger for Saharan dust than Arabian dust at different wavelengths of 440 nm and 675 nm using the AERONET inversion outputs. Córdoba-Jabonero et al [38] compared lidar ratios for Saharan dust and Arabian dust retrieved by a synergetic use of the micro-pulse lidar and AERONET measurements. Their mean lidar ratios are 54 ± 5 sr for Saharan dust and 46 ± 2 sr for Arabian dust.…”
Section: Resultsmentioning
confidence: 99%